Estimation of diffusivity from densification data obtained during spark plasma sintering. (1st March 2019) - Chawake, Niraj; Ghosh, Pradipta; Raman, Lavanya; Srivastav, Ajeet K.; Paul, Tanaji; Harimkar, Sandip P.; Eckert, Jürgen; Kottada, Ravi Sankar
Abstract: Evaluation of the diffusion coefficient of metal powders was attempted by using the power-law creep model in conjunction with the isothermal densification kinetics during spark plasma sintering (SPS). The diffusion coefficients obtained from the densification data of elemental Fe, Ni and Al powders are found to be higher than those reported in the literature. The higher values of diffusivity can be attributed to electric current effects. Our analysis demonstrates that it is possible to evaluate diffusion coefficients from experimental SPS densification data. Graphical abstract: